2014
DOI: 10.5219/332
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and fatty acids profile of chia (Salvia hispanica L.) and flax (Linum usitatissimum L.) seed

Abstract: The seeds of most plants are rich in various nutrients and can provide a lot of useful health benefits. The objective of this study was to determine and compare differences in fat, fatty acids, crude protein and amino acids concentrations for chia and flax seeds. Study was carried out using brown and gold seeds of Flax (Linum usitatissimum L.) and Chia (Salvia hispanica L.). The mean protein content in tested seeds ranged from 211.8 to 252.5 g/kg dry matter and in chia seed was about 13.10% higher than the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
11
32
4
Order By: Relevance
“…The content of fatty acids in quinoa obtained in the current investigation is relevant to the reported by Palombini et al (2013). Nitrayová et al (2014) have documented the fatty acid profile of linseed and chia seeds as follows: linolenic acid constituted on average 54.38% of the total fatty acids of linseeds and 63.79% of chia seed, and for linoleic acid it was 15.30% and 18.89%. The currently established results show a higher content of linolenic acid in chia and lower in linseed.…”
Section: Fatty Acid and Mineral Compositionsupporting
confidence: 83%
See 1 more Smart Citation
“…The content of fatty acids in quinoa obtained in the current investigation is relevant to the reported by Palombini et al (2013). Nitrayová et al (2014) have documented the fatty acid profile of linseed and chia seeds as follows: linolenic acid constituted on average 54.38% of the total fatty acids of linseeds and 63.79% of chia seed, and for linoleic acid it was 15.30% and 18.89%. The currently established results show a higher content of linolenic acid in chia and lower in linseed.…”
Section: Fatty Acid and Mineral Compositionsupporting
confidence: 83%
“…The currently established results show a higher content of linolenic acid in chia and lower in linseed. The content of linoleic acid was established to be in a 1:1,23 (chia) and 1:1,29 higher content ratio compared to the results published by Nitrayová et al (2014). A major part of the composition of fatty acids in einkorn wheat reported by Demir et al (2015) was linoleic (49.43%), oleic (34.34%) and palmitic acid (10.27%).…”
Section: Fatty Acid and Mineral Compositionmentioning
confidence: 60%
“…properties (Gałkowska, Fortuna, & Prochwicz-zagórska, 2010 (Timilsena et al, 2016;Valdivia-López & Tecante, 2015). Studies have also shown that chia seeds contain both essential amino acids and non-essential amino acids such as methionine, phenylalanine, cysteine, and glycine in significant amounts, giving it a high protein quality score (Ding et al, 2018;Nitrayová et al, 2014), and hence, it can be used to supplement low protein quality products such as pineapple jam.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber is thus one of the functional components that could be derived from chia seeds when added to pineapple jam. Chia seeds contain 30.7% fat of which palmitic (7.04%), stearic (2.84%), oleic (7.30%), linoleic (18.89%), α-linolenic (63.79%), and arachidic (0.02%) fatty acids are present (Nitrayová et al, 2014). The presence of the essential fatty acids especially αlinolenic in substantial amounts indicates that consumption of chia seeds can reduce coronary heart diseases and thus its inclusion in pineapple jam confers it with beneficial functional components.…”
Section: Discussionmentioning
confidence: 99%
“…Pork is considered to be a main source of SFA, but the content of FAs can be changed by suitable dietary manipulations to pigs nutrition (ČERVEK et al, 2011). Linseed is a rich source of n-3 FA, particularly of α-linolenic acid (NITRAYOVÁ et al, 2014) from which n-3 FA with longer chain, EPA and DHA, are metabolized. The supplementation of linseed oil into the diet of pigs increased the content of α-linolenic acid in meat (ČERVEK et al, 2011).…”
Section: Discussionmentioning
confidence: 99%